2006
DOI: 10.1103/physrevd.74.025015
|View full text |Cite|
|
Sign up to set email alerts
|

Generalizing the soldering procedure

Abstract: We start this work by revisiting the problem of the soldering of two chiral Schwinger models of opposite chiralities. We verify that, different from what one can conclude from the current literature, the usual sum of these models is, in fact, gauge invariant and corresponds to a composite model, where the component models are the vector and axial Schwinger models. As a consequence, we reinterpret this formalism as a kind of degree of freedom reduction mechanism. This result has led us to discover a second sold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 36 publications
6
54
0
Order By: Relevance
“…The field ψ μνλ corresponds to a new totally symmetric field. It is trivial to observe that with the shift ψ → ψ + φ we have the correspondence S M ⇔ S S D (3) . Using the property…”
Section: Master Action In Terms Of Totally Symmetric Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…The field ψ μνλ corresponds to a new totally symmetric field. It is trivial to observe that with the shift ψ → ψ + φ we have the correspondence S M ⇔ S S D (3) . Using the property…”
Section: Master Action In Terms Of Totally Symmetric Fieldsmentioning
confidence: 99%
“…The Lagrangian density L (3) S D stands for both the linearized topologically massive gravity of [14] and the third-order spin-3 model of [9]. Finally L (4) S D may represent either the linearized version of the higher derivative topologically massive gravity of [5,16] or the spin-3 fourth-order model whose main equations of motion are given in [10] and the whole action in [6].…”
Section: (K)mentioning
confidence: 99%
See 1 more Smart Citation
“…In some approaches, the price to be paid is the lost of locality [39]. For the case of a spin-2 self-dual field in three spacetime dimensions, it was shown that the dual model achieved by NDM does not suffer with the presence of ghosts [42].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatives to avoid the emergency of ghosts in the process of dualization were developed [39], [40], [41], [42]. In some approaches, the price to be paid is the lost of locality [39].…”
Section: Introductionmentioning
confidence: 99%